Little value creation, articulation and propagating forces: A hypothesis for the Mexican manufacturing sector - Santiago Roca Tavella; Luis Simabuko Nako (Journal of Economics, Finance and Administrative Science, 2015)
This paper evaluates the impact of Mexican trade and productive integration processes during the last 20 years. It finds evidence that growing per capita income in Mexico is directly related to its “trade opening”, but is inversely related to the growth of its manufacturing export industry. Specifically, for each point of growth in “trade opening” (as a proportion of GDP) per capita income grew by 0.22%; while each point of increase in the share of industrial exports reduced income per person by 0.09%. To explain this apparent contradiction between the positive effect of “trade opening” and the negative impact of productive manufacturing specialization, we examined the characteristics of Mexico's industry. Results show that although Mexico's export-led industrialization successfully adapted to the world market and transformed its productive, business, organizational and technological structure, it did not translate into adequate macroeconomic benefits due to the absence of strong value dissemination forces over the rest of the economy. In this sense, poor internal linkages in the maquila industry, its high propensity to import, and its limited value added generation, among other elements, led the Mexican industry to operate as an export enclave. In those circumstances, manufacturing does not generates positive externalities nor articulations, nor strong disseminations that increase and multiplies value in other sectors of industry, thus limiting expansion effects and restraining or even reducing–under some specific circumstances–per capita income growth. – – Este documento evalúa el impacto del comercio y los procesos de integración productiva de México durante los últimos veinte a\~nos. Aporta evidencia acerca de que el crecimiento de la renta per cápita en México se halla directamente relacionado con su “apertura comercial”, aunque guarda una relación inversa con el crecimiento de su industria de exportación manufacturera. De modo específico, para cada punto de crecimiento de la “apertura comercial” (como proporción del PIB), la renta per cápita creció un 0.22%, mientras que cada punto de incremento de la cuota de exportaciones industriales redujo la renta per cápita en un 0.09%. Para explicar esta aparente contradicción entre el efecto positivo de la “apertura comercial” y el impacto negativo de la especialización manufacturera productiva, examinamos las características de la industria mexicana. Los resultados muestran que aunque la industrialización impulsada por la exportación de México se ha adaptado exitosamente al mercado mundial, transformando su estructura productiva, comercial, organizativa y tecnológica, ello no se ha traducido en los beneficios macroeconómicos adecuados, debido a la ausencia de unas sólidas fuerzas de diseminación del valor sobre el resto de la economía. En este sentido, los débiles vínculos internos en la industria de maquila, su elevada propensión a la importación, y su limitada generación de valor a\~nadido, entre otros elementos, han llevado a la industria mexicana a operar como un enclave exportador. En estas circunstancias, la fabricación no genera externalidades ni articulaciones, ni fuertes diseminaciones que incrementen y multipliquen el valor en otros sectores de la industria, limitando, por tanto, los efectos de expansión, así como restringiendo, e incluso reduciendo, bajo circunstancias específicas, el crecimiento de la renta per cápita.
Keywords: O14; 330; Industrialization; Technological change; Industrial policy; Trade; Latin America; Industrialización; Cambio tecnológico; Política industrial; Comercio; Latinoamérica